Ḥamzah Fanṣūrī’s Contextual Analogies: Wujūdiyya Teaching in Malay 16th Century - Miswari Miswari; Abdul Aziz Dahlan; Abdul Hadi W.M. (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2022)
Abstract: This article aims to analyse the context of the analogies used by Ḥamzah Fanșūrī in teaching wujūdiyya doctrine in his work, Asrār al-‘Ārifīn. The importance of this study is to reveal how he easily taught complex metaphysical concepts in Sufism. He used objects easily recognised by the Malay community as analogies. This article is a literature study using an analytical-descriptive approach. This study found that the metaphors used by Ḥamzah Fanșūrī in teaching the relationship between singularity and plurality in ujūdiyya doctrine were clay and earthen vessels, sun and its light, wood and chess pieces, and sea and wave. In comparison, secondary analogies such as fruit, seeds, mirrors, people, rivers, stones, and iron were used to explain the various dimensions of wujūdiyya teachings. His approach is therefore easy to understand.Contribution: This article opens a new perspective in understanding Sufism, especially the wujūdiyya doctrine in Ḥamzah Fanșūrī’s teaching. The analogies used are easy to understand. The analogy proposed by Ḥamzah Fanșūrī can be used as a reference to reveal the metaphors used by other Sufis in teaching wujūdiyya.